Early detection of cervical cancer using deep neural networks - Akhund, Atoshi; Ahmad, Saad; Taki, Sarwar Siddiqui (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.